The impact of corporate characteristics on the level of environmental disclosure considering the requirements of the Saudi Capital Market Authority: An applied study of Saudi energy companies - Alshehri, Mohammed Hamoud; Alosaimi, Meshary Hamdan (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aims to determine the level of environmental disclosure for Saudi energy companies considering the requirements of the Saudi Capital Market Authority, in addition to identifying the impact of the characteristics of companies on the level of environmental disclosure., The age of the company on environmental disclosure for the year 2021. The study population was represented by Saudi energy companies and by using the content analysis of the reports of the board of directors according to the environmental disclosure index issued by the Saudi financial market, the level of disclosure was calculated, which showed the low disclosure rate, where the average value of the level of environmental disclosure for sector companies Energy 36.6%, and using regression analysis, the study concluded that there was no effect of the company’s characteristics, size, age, and profitability of the company on the level of environmental disclosure.